Universities and Their Leadership - Shapiro, Harold T., 1935-; Bowen, William G. (Book collections on Project MUSE., 1998)
On the occasion of the 250th anniversary of Princeton University, leading educators and commentators participated in a symposium jointly sponsored by Princeton and The Andrew W. Mellon Foundation. Universities and Their Leadership is a collection of original essays from presenters at the Princeton Conference on Higher Education. Individually, these essays discuss aspects of contemporary higher education in the U.S. Taken together, they offer a useful perspective on issues that face American universities as they enter the twenty-first century. The opening essay, "The University and Its Critics" by Frank Rhodes, confronts criticisms of the American university, examines how universities have changed over recent decades, and suggests a plan of action to restore public confidence and strengthen bonds of community within universities. "On the Accountability of Higher Education in the United States," by Martin Trow, deals with the critical issue of responsibility. Harold Shapiro's essay, "University Presidents--Then and Now," blends personal insights with a historical account of changes over time in the roles of university presidents. In commenting on Shapiro's paper, Hanna Gray draws on her experiences as a university president and her training as a historian to demonstrate that university presidents have always operated under constraints. Henry Rosovsky and Inge-Lise Ameer collaborate in the essay "A Neglected Topic: Professional Conduct of College and University Teachers," to which Amy Gutmann responds in an essay entitled "How Can Universities Teach Professional Ethics?" Oliver Fulton contributes a cross-cultural perspective in "Unity or Fragmentation, Convergence or Diversity: The Academic Profession in Comparative Perspective in the Era of Mass Higher Education." Daniel J. Kevles's essay, "A Time for Audacity: What the Past Has to Teach the Present about Science and the Federal Government," considers the historical partnership between the scienti